Features of Neck Pain and its Related Factors Among Patients With Cervical Spondylosis - Nayeema Binti Karim; Aklima Chowdhury Asha; Md. Aminul Islam; Anup Mandal; Taslima Islam; Kh. Shafiur Rahaman (Shahrekord University of Medical Sciences, 2018)
Background and aims: The prevalence of cervical spondylosis is rising. The objective of this study was to figure out the various features and their related factors among cervical spondylosis patients in Dhaka, Bangladesh. Methods: A descriptive cross-sectional study was conducted enrolling 40 patients from NITOR (National Institute of Traumatology and Orthopedic Rehabilitation) in Dhaka, Bangladesh. Data were collected from the physiotherapy department of NITOR using convenient sampling technique. A structured questionnaire was used for data collection. Patients who were diagnosed with cervical spondylosis were included in this study. Data were analyzed using SPSS version 22.0. Descriptive analysis was done using frequency measures, mean and percentages. Results: Among our respondents, the majority of them were female (62.5%). Majority of the participants were in the age group of 35 to 50 years (62.5%). Many of them were urban population engaged in service or housewives. Stressful job (55%), duration of working hour >8 hours (62.5%) were the most common characteristics among patients. The main location of pain was in the shoulder (82.5%) followed by the neck (77.4%) and forearm (70%). Most patients had intermittent pain (57.5%), numbness (55%), tingling sensation (47.5%) and paresthesia (42.5%). Moderate type of pain (65%), the involvement of both upper limbs (35%) and radiating pain to shoulder (72.5%) were the most reported features by patients. No response to medication was also observed. Conclusion: Being female, middle age group, stressful occupation, location and radiation of pain to shoulder are some of the common features revealed in this study. The findings will help the practitioner to plan their treatment goals and techniques considering the characteristics of patients.